Forest Ecosystem Services Contribution in the Sustainable Development Goals: A Case Study from the Western Ghats Region in Karnataka - Balasubramanian, M. (Indian Forester, 2021)
The main objective of the study is to establish the connection between forest ecosystem services (poverty and hunger reduction, valuation of different ecosystem services, sustainable consumption) and sustainable development goals in the Western Ghats region in Karnataka. The present study has used both primary and secondary data to establish the linkages between forest ecosystem services and Sustainable Development Goals (SDGs). The information of Non-Timber Forest Products (NTFPs) collection, consumption and economic valuation have been obtained through the household survey from 148 tribal households from Biligiri Rangasawmy and Nagarhole National Park in the Western Ghats in Karnataka. The valuation of recreation services was undertaken through the travel cost method from the 275 tourist visitors of the both wildlife sanctuary. The total value of ecosystem services at the ₹ 52.61 million for 2018. The highest contribution carbon sequestration at 29 million was from followed by recreation services at ₹ 7.8 million, provisioning services at 3.6 million and soil erosion prevention at ₹ 2.18 million in the both protected areas in the Western Ghats in Karnataka. The major policy implication of the study is the understanding, importance and valuation of forest ecosystem services for designing local land use management as well as sustainable livelihood of poor.